PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. DASAR RUKUN - Nur Eka Fathona; Chaterina Yunita Tarigan (Human Capital Development, 2017)
Purpose- This study aims to determine the influence of competence and work discipline on the performance of employee in PT. Dasar Rukun. Design/methodology/approach- Variable in this research consisting of the independent variable are competence and work discipline the dependent variable is the employee performance. The kind of data that would check the primary data. A population that used in this research was all the employees PT. Dasar Rukun. Data were collected and analyzed using SPSS versions 20. Findings- The results showed that the competence and work discipline has positive and significant effect on employee performance. This means the employee's performance will be better if they have higher competence and discipline and employability.